Mannose-binding lectin gene polymorphism in systemic lupus erythematosus nephritis - Osama Sayed Daif Allah; Alshimaa Hafez Abdelall; Madeha Mahrous Zakhary; Nagwa S. Ahmed; Asmaa Mohamed Goda (Journal of Biochemical and Clinical Genetics, 2021)
Background: Systemic lupus erythematosus (SLE) is a complex trait characterized by the production of a range of autoantibodies and a diverse set of clinical phenotypes, including skin rash, neuropsychiatric and musculoskeletal symptoms, and lupus nephritis (LN). Mannan-binding lectin (MBL) is a recognition molecule of the lectin pathway of complement activation. We investigated MBL gene polymorphism at exon 1 codon 54 as a potential biomarker for SLE nephritis in the current study. Methodology: A casecontrol study screened 70 participants. They were included in the study from the outpatient clinic or the inpatient section of the Rheumatology Department at Sohag University Hospital during July 2017-June 2019 for MBL gene polymorphism at exon 1 codon 54, which was detected by polymerase chain reaction using sequence-specific priming. Result: There was a predominance of AA (wild) genotype in the control group (40%). Patient groups had a statistically significant equal higher frequency of heterozygous polymorphism (AB) (76%) than the controls. BB genotype showed a statistically significant lowest frequency in the LN group (p-value = 0.04). Conclusions: MBL AB genotyping was more frequent in SLE patients either with or without nephritis than in the normal Egyptian population. BB genotyping was less frequent in LN patients than in patients without nephritis. The present study supports that the carriage of MBL AB genotype (heterozygous polymorphism at codon 54) was associated with both SLE and LN development in normal Egyptians. [JBCGenetics 2021; 4(1.000): 14-21]